Assessing the catastrophic effects of out-of-pocket healthcare payments prior to the uptake of a nationwide health insurance scheme in Ghana - James Akazili; Diane McIntyre; Edmund W. Kanmiki; John Gyapong; Abraham Oduro; Osman Sankoh; John E. Ataguba (Taylor & Francis Group, 2017)
Background: Financial risk protection against the cost of unforeseen healthcare has gained global attention in recent years. Although Ghana implemented a nationwide health insurance scheme with a goal of reducing financial barriers to accessing healthcare and addressing impoverishing effects of out-of-pocket (OOP) healthcare payments, there is a paucity of knowledge on the extent of financial catastrophe of such payments in Ghana. Thus, this paper assesses the catastrophic effect of OOP healthcare payments in Ghana. Methods: Ghana Living Standard Survey (GLSS 5) data collected in 2005/2006 are used in this study. Catastrophic effect of OOP healthcare payments is assessed using various thresholds of total household expenditure and non-food expenditure. Furthermore, four indices, namely the catastrophic payment headcount, catastrophic payment gap, weighted catastrophic payment headcount and weighted catastrophic payment gap, are defined and computed. Results: As at 2005/2006, it was estimated that 11.0% of households in Ghana spent over 5% of their total household expenditure on healthcare OOP. However, after adjusting for the concentration of such spending, it decreased to 10.9%. Also 10.7% of households spent more than 10% of their non-food consumption expenditure on OOP healthcare payments. Furthermore, about 2.6% of households are observed to have spent in excess of 20% of their total household income on healthcare OOP. With the exception of the 5% threshold of household expenditure, because the concentration indices of these expenditures are negative, the burden of such expenditures rests more on the poor. Conclusions: Significant levels of financial catastrophe existed in Ghana prior to the uptake of the national health insurance scheme. Poorer households were at a higher risk than the relatively well-off households. The results of this study present baseline assessment of the impact of Ghana's health insurance policy on catastrophic healthcare payments. Thus, there is a need for continuous monitoring of financial catastrophe in the system to ensure that households are adequately protected.